Does Regulatory Governance Matter for Financial System Stability? : An Empirical Analysis - Das, Udaibir; Chenard, Kina.; Quintyn, Marc. (Washington, D.C. : International Monetary Fund, 2004)
This paper provides empirical evidence that the quality of regulatory governance-governance practices adopted by financial system regulators and supervisors-matters for financial system soundness. The paper constructs indices of financial system soundness and regulatory governance, based on country data collected from the Financial Sector Assessment Program (FSAP). Regression results indicate that regulatory governance has a significant influence on financial system soundness, along with variables reflecting macroeconomic conditions, the structure of the banking system, and the quality of political institutions and public sector governance. The results also indicate that good public sector governance amplifies the impact of regulatory governance on financial system soundness.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet